Peran Faktor Pendorong Pada Keputusan Berkunjung Ke Kebun Raya Bogor - Yuviani Kusumawardhani; Alma Alviana (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2021)
Bogor Botanical Garden is one of the icons of the Bogor City. Bogor Botanical Garden is a tourist site that has a forest concept but is located in the center of Bogor City so that access to Bogor Botanical Garden is easily accessible. Bogor Botanical Gardens is located in Ir. H. Juanda number 13, Bogor, West Java, Indonesia. This study was conducted to determine the effect of the Motivation Driving Factor on the Decision to Visit in Bogor Botanical Garden.This research uses quantitative research, with descriptive methods. Many of the samples studied were 100 respondents who had visited Bogor Botanical Gardens.Based on the results of the study it was concluded that from the results of the hypothesis test (T-Test) conducted by the researcher produced a tcount of 10.463> Ttable 1.98447. This shows that there is a significant influence between the Motivating Factors for Visiting Decisions. The influence of motivating factors on the decision to visit Bogor Botanical Gardens with a strong correlation coefficient of 0.726 because it is between 0.600-0.799. The coefficient of determination or the percentage of influence of the Factors Driving Tourist Motivation (X) Decision to Visit (Y) is 52.8%. Meanwhile, the remaining 47.2% is influenced by other variables not examined in this research.